Here, there,... et le processus référentiel - Patrice Larroque (Anglophonia)
There is a general tendency to think that here is the starting point of reference. The pairs here/there and this/that, for instance, are named in the proximal/distal order, which gives the impression that relative placement is assessed from the center outwards.In this paper I hypothesize that, as regards reference, there precedes here and that implies this, suggesting a centripetal process pulling in to the center and the speaker’s sphere. Thus the locating and referential operators used by the utterer represent the peripheral situation in the first place. In some non-standard varieties of English the mere evocation of the situational items brings out their existence, an existence which can be negated by the deletion of the reference point and its trace in the utterance.